Modeling and simulation of the aqueous humor flow in the human eye - Dörsam, Simon; Olkhovskiy, Vladislav; Friedmann, Elfriede (Proceedings in applied mathematics and mechanics, 2019)
A mathematical model for the physiology of the aqueous humor flow in the human eye is developed. The governing equations are the Stokes and Darcy equations with certain physical characteristic parame...